2006
DOI: 10.1007/s00280-006-0228-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of cyclooxygenase-mediated prostaglandin production by the putative cancer chemopreventive flavonoids tricin, apigenin and quercetin

Abstract: The results demonstrate that these structurally similar flavonoids regulate COX-mediated PGE-2 production in different fashions. Their ability to attenuate prostanoid levels may contribute to their cancer chemopreventive efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 20 publications
4
54
2
1
Order By: Relevance
“…1), which occurs in rice bran and other grass species, and its closely related cogener apigenin (4',5,7-trihydroxyflavone, see Fig. 1) from leafy vegetables were recently shown to interfere effectively with prostaglandin generation in human colorectal cells [3]. This paper suggests that the two flavones exert an effect on prostaglandin production via differential mechanisms, tricin by inhibition of cyclooxygenase (COX) enzyme activity, and apigenin by downregulation of COX-2 expression.…”
Section: Introductionmentioning
confidence: 90%
“…1), which occurs in rice bran and other grass species, and its closely related cogener apigenin (4',5,7-trihydroxyflavone, see Fig. 1) from leafy vegetables were recently shown to interfere effectively with prostaglandin generation in human colorectal cells [3]. This paper suggests that the two flavones exert an effect on prostaglandin production via differential mechanisms, tricin by inhibition of cyclooxygenase (COX) enzyme activity, and apigenin by downregulation of COX-2 expression.…”
Section: Introductionmentioning
confidence: 90%
“…In addition, the results that dietary tricin lowered the ABI of adenocarcinoma cells suggest that tricin affects the chromosomal instability of cancer cells and possibly their telomerase activity (41). Tricin may exert chemopreventive activity through inhibition of COX-1 and 2 enzymes and prostaglandin E 2 production in human colon cancer cell lines (HT-29 and HCA-7) and the small intestine of Apc Min/+ mice (23,24). Unexpectedly, dietary tricin did not significantly alter the expression of COX-2 or iNOS at week 8.…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports on the effects of dietary tricin on intestinal carcinogenesis. Cai et al (23) reported that feeding a diet containing 0.2% tricin decreased the size and the number of intestinal adenoma formed in Apc Min/+ mice through the inhibition of cyclooxygenase (COX)-2 (23,24). Dietary tricin did not affect tumor formation in the large bowel (23).…”
mentioning
confidence: 99%
“…This has been shown for epicatechingallate, quercetin, resveratrol and genistein in colon cells in vitro. 39,40 In addition to the capacity of AE to modulate detoxification related genes, AE also seemed to modulate several other genes spotted on the custom array that are related to important functions such as, tumor suppression, cell cycle control, cell signaling as well as apoptosis. For instance, AE increased the expression of 5 established or candidate tumor suppressor genes namely, BRCA2, PTPRT, PTPN6, PTPRN and PTPRJ (Dep-1) in LT97 cells.…”
Section: Discussionmentioning
confidence: 99%